ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA MINAT BELAJAR SAINS SISWA KELAS V SEKOLAH DASAR NEGERI 008 LANGGINI - Wahyu Andriani; Ramdhan Witarsa; Nurmalina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes the factors that influence the students’ low interest in natural science learning subjects at Public Elementary School 008 Langgini. The type of research was qualitative research with a descriptive approach. The subjects involved 21 fifth-grade students at Public Elementary School 008 Langgini. Data collection tools used were an observation sheet, an interview sheet as primary data, and some documentation as the supporting data. The results of the study indicated that the factors that influence the students’ interest in natural science learning subjects at grade V of Public Elementary School 008 Langgini were the pleasure of students in participating the learning process only at 42.8% and 57.1% of students who looked not cheerful when the teacher conveyed the learning material. Students' attention to learning could be seen from the students who focused and did not pay attention when other students passed by outside the classroom only 14.2% and 85.7% of students were unable to concentrate. The students’ involvement, which was seen from students who actively asked if they did not understand the lesson conveyed by the teacher, was only 19.0% and 80.9% of students who did not want to ask if there was a subject matter that was not understood. The results also indicated that factors that influenced students’ interest in science learning subjects at grade V of SDN 008 Langgini included internal factors, which were lack of pleasure, attention and lack of students involved in science learning. External factors were monotonous science learning subject, the learning was still focused on the teacher, and the learning materials that were still memorized and difficult to be understood. Thus, the factors that influenced the students’ low interest in science learning subject are important to note.